2020
DOI: 10.1080/15384047.2020.1779005
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the intestinal GUCY2C tumor suppressor axis requires APC loss of heterozygosity

Abstract: Most sporadic colorectal cancer reflects acquired mutations in the adenomatous polyposis coli (APC) tumor suppressor gene, while germline heterozygosity for mutant APC produces the autosomal dominant disorder Familial Adenomatous Polyposis (FAP) with a predisposition to colorectal cancer. In these syndromes, loss of heterozygosity (LOH) silences the remaining normal allele of APC, through an unknown mechanism, as the initiating step in transformation. Guanylyl cyclase C receptor (GUCY2C) and its hormones, urog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…[22][23][24] However, transformation universally orphans the receptor through loss of hormones. 7,16,[21][22][23]25,26 Hormone loss silencing GUCY2C occurs early in dysplastic crypts and is conserved across species and tumor subtypes. 16,22,23,25,26 GUCA2A is lost following APC inactivation in mouse models of conditional biallelic Apc deletion (Apc CKO/CKO ) and Apc loss of heterozygosity (Apc min/þ ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] However, transformation universally orphans the receptor through loss of hormones. 7,16,[21][22][23]25,26 Hormone loss silencing GUCY2C occurs early in dysplastic crypts and is conserved across species and tumor subtypes. 16,22,23,25,26 GUCA2A is lost following APC inactivation in mouse models of conditional biallelic Apc deletion (Apc CKO/CKO ) and Apc loss of heterozygosity (Apc min/þ ).…”
Section: Methodsmentioning
confidence: 99%
“…7,16,[21][22][23]25,26 Hormone loss silencing GUCY2C occurs early in dysplastic crypts and is conserved across species and tumor subtypes. 16,22,23,25,26 GUCA2A is lost following APC inactivation in mouse models of conditional biallelic Apc deletion (Apc CKO/CKO ) and Apc loss of heterozygosity (Apc min/þ ). Further, silencing mutant b-catenin-TCF signaling restores GUCA2A levels.…”
Section: Methodsmentioning
confidence: 99%
“…As the receptor for the heat-stable enterotoxin, and for endogenous paracrine ligands uroguanylin and guanylin, GCC has a clear role in intestinal fluid homeostasis. GCC also has a role as a tumor suppressor and biomarker [12][13][14] with GCC targeting as therapy for oncologic and gastrointestinal disorders. [15][16][17][18][19][20] GCC is also a focus of satiety and obesity studies because of the observation that it is a satiety modulator with activation relative to serum pro-uroguanylin levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, an alternative hypothesis suggests that APC loss of heterozygosity precedes guanylin loss, necessarily lifting a barrier to tumorigenesis imposed by GUCY2C. A recent pair of studies demonstrated that guanylin is comparably expressed in wild type and APC min/+ mice, and is only lost following biallelic APC deletion, suggesting that guanylin expression is unable to prevent sporadic APC loss of heterozygosity [16,17]. Reconstitution of wild type APC in colorectal cancer cells was sufficient to restore guanylin expression in vitro, supporting the hypothesis that APC loss drives guanylin loss [16].…”
Section: Expert Opinionmentioning
confidence: 99%